Study on Bond Strength of Alccofine Based Normal and High Strength Concrete - Balamuralikrishnan R.; Saravanan J. (Salehan Institute of Higher Education, 2019)
Plenty of research works in India and abroad focusing on the reuse or recycling of waste materials from many industries. Among that finding out suitable cementitious material for the replacement of cement is significant. Many waste materials such as fly ash, silica fume, GGBS, metakaoline, micro materials, quartz power, etc. are tried out for replacing partially or full of cement in concrete. A new ultrafine material called Alccofine is tried out for replacing partially in this research. M20 and M60 grade of concrete is intended to study the performance of normal and high strength concrete by replacing the cement with alccofine of different dosages. Previous researches showed that the replacement of alccofine increases the strength. Design mix made for M20 and M60 grade and cubes casted with various percentage of alccofine with cement. Hence the study is aimed to assess the bond behavior of M20 and M60 grade of concrete structures as an alternate to the conventional materials. The cubes are prepared initially for the design mix and determined the strength of concrete. Then specimens are prepared for the bond test and tested using pullout test methods. The results are analyzed and observed that the bond strength is increased with increase of alccofine replacement to certain dosage.